9 Corticosteroid use in periorbital and orbital cellulitis: A Cochrane systematic review. (19th August 2020) - Kornelsen, Emily; Mahant, Sanjay; Parkin, Patricia C; Reginald, Arun; Shah, Samir S; Gill, Peter J
Abstract: Background: There is significant variation in the use of corticosteroids for the treatment of periorbital and orbital cellulitis. Corticosteroids may act to reduce inflammation and edema but there are concerns that corticosteroids may lead to immune suppression and worsening infection. Evidence-based recommendations regarding the use of corticosteroids for periorbital and orbital cellulitis are lacking. Objectives: To assess the effectiveness and safety of corticosteroids in the treatment of periorbital and orbital cellulitis. Design/Methods: We conducted a detailed search of MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), CINAHL Plus, ClinicalTrials.gov, and the World Health Organization (WHO) International Clinical Trials Registry Platform for randomized controlled trials (RCTs) of children and adults with periorbital and orbital cellulitis treated with systemic or intranasal corticosteroids. There were no exclusions based on language or publication status. Studies were excluded if they focused exclusively on participants undergoing elective surgery, on post-operative infections, or infections secondary to trauma. Two reviewers independently assessed studies for inclusion, and extracted data in duplicate. Risk of bias was assessed using the Cochrane Collaboration's domain-based evaluation tool. Data were analyzed according to standard Cochrane methodology. Results: Of the 7, 476 unique results identified, 7, 465 records were excluded based on title and abstract screening, and a further 10 records were excluded based on full text review. We identified one small RCT conducted in India with an unclear risk of bias. No other eligible ongoing or completed trials were identified. The small trial of 21 participants 10 years and older compared the use of corticosteroids and antibiotics (n=14), to the use of antibiotics alone for the treatment of orbital cellulitis (n=7). Participants receiving corticosteroids had a shorter length of hospital stay (14.1 ±3.7 vs. 18.4 ±5.9 days, p=0.02) and required antibiotics for a shorter duration (8.6 ±1.3 vs. 11.6 ±4.6 days, p=0.013) compared with the control group. Earlier improvements in fever, pain, periorbital edema, extra ocular motility, conjunctival chemosis, and visual acuity were seen in the corticosteroid group. No major complications of orbital cellulitis or adverse effects of corticosteroids were reported. Conclusion: There is insufficient evidence to draw conclusions about the use of corticosteroids in the treatment of periorbital and orbital cellulitis. Currently, there is significant variation in how corticosteroids are used in clinical practice and additional high-quality evidence is needed to inform decision making.